A tutela preventiva como meio adequado para uma efetiva proteção do meio ambiente do trabalho sadio - Zuliani, Aldo Marcelo (My University, 2024)
This dissertation deals with the protection of the health of the working environment, aiming to find forms of preventive judicial protection. The general objective is to reduce litigation in social security lawsuits, filed individually against the National Social Security Institute, which postulates the recognition of exposure to unhealthy contraband agents in the working environment of companies, for the purpose of granting contribution benefits with pecuniary contribution time. The guiding question of the research was the collectivization of judicial protection granted in such individual processes. Based on this question, two forms of collectivization were analyzed: the expansion of the effects of proof of exposure to unhealthy agents in the work environment, including companies in the individual process; or communication to the Public Ministry of Labor and/or the Occupational Safety Secretariat for measures, in other areas, against companies that violate occupational health standards. It was concluded that these alternatives have the potential to reduce litigation, representing adequate means to provide preventive and more effective protection to the work environment. [resumo fornecido pelo autor]
Esta dissertação trata sobre a proteção da higidez do meio ambiente do trabalho, visando ao encontro de formas de tutela judicial preventiva. O objetivo geral é a redução da litigiosidade em processos judiciais previdenciários, ajuizados individualmente contra o INSS, em que se postula o reconhecimento da exposição a agentes nocivos insalubres no ambiente laboral de empresas, para fins de concessão de benefícios de aposentadoria.A questão orientadora da pesquisa foi a coletivização da tutela judicial concedida em tais processos individuais. A partir desta questão, foram analisadas duas formas de coletivização: a ampliação dos efeitos da prova de exposição a agentes nocivos insalubres no meio ambiente de trabalho, incluindo-se as empresas no processo individual; ou a comunicação ao Ministério Público do Trabalho e/ou à Secretaria de Segurança do Trabalho para providências, em outros âmbitos, contra as empresas infratoras das normas de saúde do trabalho. Concluiu-se que essas alternativas têm potencial para reduzir a litigiosidade, representando meios adequados para proporcionar uma proteção preventiva e mais efetiva ao meio ambiente do trabalho. [resumo fornecido pelo autor]
Keywords: Ambiente de trabalho; Higiene do trabalho; Ação judicial; Aposentadoria especial; Previdência social - Legislação; Tutela; Work environment; Industrial hygiene; Actions and defenses; Special retirement; Social Security - Legislation; Guardian and ward